ETHICAL DILEMMAS OF CONTEMPORARY POLITICAL MEDIATION: ADAPTING TO MODERN CHALLENGES - Kalashlinska, Maryna (Politology bulletin, 2023)
In the contemporary global context, the role of political mediation is increasingly pivotal in resolving conflicts at every stratum, from the local to the global arena. However, amidst rapid global transformations, ethical dilemmas in mediation processes become more pronounced and demand urgent attention. This article focuses on a comprehensive examination of current ethical conundrums in political mediation. It pays particular attention to the mediator’s responsibility, the selection of strategies and methodologies that foster trust and dialogue, and a critical analysis of mediation examples that demonstrate a diversity of approaches and outcomes. The piece thoroughly investigates the broad spectrum of challenges associated with the application of ethical principles in mediation processes and attempts to discern how modern global trends and challenges affect conventional political mediation methods. It also provides a historical perspective, scrutinizing the evolution of academic perspectives on ethical dilemmas in politics through various historical epochs. The study observes that the ethical issues in contemporary political mediation and its adaptation to new challenges often remain outside the scope of scholarly discourse. This lack of adapted concepts and methodologies necessitates further academic efforts and scrutiny of ethical issues within the context of current political negotiations and mediation. The author suggests additional research into the impact of global trends, such as globalization, technological innovations, and an increase in political mediation actors, on the ethical dimensions of this sphere.

У статті розглядаються ключові етичні дилеми політичного посередництва в умовах сучасних викликів. Особлива увага приділяється питанням відповідальності медіаторів, вибору стратегій та методів роботи, що сприяють відновленню довіри та діалогу між сторонами, а також критичному аналізу прикладів медіації, які показують різноманітність підходів та результатів. Висвітлюється широкий спектр проблем, пов’язаних із застосуванням етичних принципів у процесі медіації та визначається, як сучасні глобальні тенденції та виклики впливають на традиційні підходи до політичного посередництва. Розглядається історичний контекст, шляхом аналізу еволюції наукових поглядів на етичні дилеми в політиці, а також на співвідношення між політикою та мораллю протягом різних історичних епох. Констатовано, що етичні дилеми сучасного політичного посередництва і його адаптація до новітніх викликів часто залишаються поза рамками наукового дискурсу, що вимагає додаткових наукових зусиль та уваги до етичних питань в контексті сучасних політичних переговорів та медіації. Запропоновано подальше дослідження впливу глобальних тенденцій, таких як глобалізація, технологічні інновації, збільшення кількості акторів у політичному посередництві тощо на етичні аспекти в даній сфері, з особливим акцентом на розвиток та впровадження нових моделей та підходів, які враховують ці складні зміни.
ЕТИЧНІ ДИЛЕМИ СУЧАСНОГО ПОЛІТИЧНОГО ПОСЕРЕДНИЦТВА: АДАПТАЦІЯ ДО СУЧАСНИХ ВИКЛИКІВ
Keywords: political mediation; ethics; mediation; globalization; technological innovations; conflict resolution; dilemmas; geopolitical processes; політичне посередництво; етика; медіація; глобалізація; технологічні інновації; врегулювання конфліктів; дилеми; геополітичні процеси